2022
DOI: 10.1002/admi.202200194
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization‐Enhanced Stability by Effectively Suppressing Photooxidation Defect for Optoelectronic Devices

Abstract: Effective protection against photooxidation of organic wide‐bandgap semiconductors is a potential method to afford high efficient deep‐blue emission for full color displays. Herein, the crystallization effect of fluorene‐based blue emitter on suppressing the formation of long‐wavelength green band (g‐band) defect is demonstrated through the model of self‐assembled organic micro/nanocrystals. The selected molecule 2,2'‐bi(9,9‐dipropyl)fluorene (DDC3F), which easily generates strong g‐band emission (green index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…5f). These observations suggested that DWG1 exhibited crystal-induced luminescence enhancement feature, [46][47][48][49] while TWG1 did not, probably due to its tighter arrangement in the crystalline (the density of single crystals: 1.335 gcm -3 , 1.296 gcm -3 , 1.238 gcm -3 and 1.081 gcm -3 for meso-DWG, rac-DWG1, cis-cis-TWG1 and cis-trans-TWG1, respectively) and strong intermolecular interactions, effectively suppressing the nonradiative relaxation process. Interestingly, these results contradict the phenomenon of red-shifted and quenched emission observed in most luminescence due to exciton coupling, orbital overlap, and π-π aggregation as pressure increases.…”
Section: Resultsmentioning
confidence: 85%
“…5f). These observations suggested that DWG1 exhibited crystal-induced luminescence enhancement feature, [46][47][48][49] while TWG1 did not, probably due to its tighter arrangement in the crystalline (the density of single crystals: 1.335 gcm -3 , 1.296 gcm -3 , 1.238 gcm -3 and 1.081 gcm -3 for meso-DWG, rac-DWG1, cis-cis-TWG1 and cis-trans-TWG1, respectively) and strong intermolecular interactions, effectively suppressing the nonradiative relaxation process. Interestingly, these results contradict the phenomenon of red-shifted and quenched emission observed in most luminescence due to exciton coupling, orbital overlap, and π-π aggregation as pressure increases.…”
Section: Resultsmentioning
confidence: 85%
“…Reproduced with permission. [186] Copyright 2022, Wiley-VCH. c) High-resolution XPS spectra of Zn 2p, Cd 3d, and S 2p of ZnS, Cd 0.4 Zn 0.6 S, and CdS based 1D NRs.…”
Section: Nrsmentioning
confidence: 99%
“…Recently, organic functional materials exhibit a wide range of promising applications in various devices with the unique combination of tunable optoelectronic properties, such as organic light-emitting diodes (OLEDs), organic photovoltaics (OPVs), organic lasers, organic field-effect transistors (OFETs), and even organic field-effect light-emitting transistors. In particular, the organic crystalline materials have been demonstrated to be more significant for enhanced device performance with features of minimized impurities and ordered molecular arrangement. , In general, the emission color of crystalline materials is both determined by molecular structures and aggregate states, which can be further finely tuned by modification of the molecular fragment or regulation of packing modes based on the noncovalent supramolecular interaction in the same building block. In fact, compared with the traditional and tedious structure synthesis based on covalent bonds, the regulation of molecular packing in the crystalline state is a simpler and lower cost method . For single-component crystalline materials, the multicolor emissive behaviors can be obtained in the polymorph states due to the different molecular conformations, through induction of solvent molecules. However, the phenomenon is extremely limited and difficult for aggregate chemistry. , Therefore, a simple and universal method specifically needs to be established to achieve multicolor emission in organic crystalline materials.…”
Section: Introductionmentioning
confidence: 99%